EFFECT OF PRATISAARANEEYA APAMARGA KSHARA IN THE MANAGEMENT OF JALARBUDA W. S. R TO MUCOCELE OF LIP-A CASE STUDY - V R Hiremath; Savadi, Basavaraj (International Journal of Research in AYUSH and Pharmaceutical Sciences, 2018)
Jalarbuda is a water bubble like growth in lip caused due to vitiation of Vata and Kapha. Ksharakarma is one of the para-surgical procedures advised for management of Jalarbuda. This condition can be correlated to mucocele of lip. This is a case report of 22 year old man who presented with a small swelling in lip associated with discomfort since one month. In this study Pratisaaraneeya Apamarga Kshara is used in management of mucocele. The size of mucocele reduced after two days of Kshara application.